2020
DOI: 10.12688/f1000research.20099.2
|View full text |Cite
|
Sign up to set email alerts
|

Salivary nitric oxide, Simplified Oral Hygiene Index, and salivary flow rate in smokers and non-smokers: a cross-sectional study

Abstract: Background: Salivary nitric oxide plays an important role as an antibacterial agent in the oral cavity. Here, we analyze salivary nitric oxide, Simplified Oral Hygiene Index (OHI-S) scores and the salivary flow rate in smokers and non-smokers which has not been done previously. Methods: A cross sectional study included 25 smokers and 25 non-smokers. Their OHI-S results were categorized as “good,” “medium,” or “bad.” Unstimulated saliva samples were collected, and their nitric oxide concentration was measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Alteration of salivary composition, including enzymes and immunoglobulins, leads to loss of defense functions and may promote plaque formation [ 102 – 104 ]. The influence of the salivary flow rate in this context has been rebutted in the study by Mokeem et al [ 57 ], whereas others demonstrated a significant reduction of salivary flow rate in smokers compared to non-smokers [ 96 , 105 ]. Possible reasons suggest a chemical-thermal degradation of nitric oxide [ 106 ], an autoregulator of salivary secretion, and a reduction of salivary secretion due to nicotine-mediated vasoconstriction [ 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of salivary composition, including enzymes and immunoglobulins, leads to loss of defense functions and may promote plaque formation [ 102 – 104 ]. The influence of the salivary flow rate in this context has been rebutted in the study by Mokeem et al [ 57 ], whereas others demonstrated a significant reduction of salivary flow rate in smokers compared to non-smokers [ 96 , 105 ]. Possible reasons suggest a chemical-thermal degradation of nitric oxide [ 106 ], an autoregulator of salivary secretion, and a reduction of salivary secretion due to nicotine-mediated vasoconstriction [ 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four healthy subjects, 20 male, 14 female, median age 35.44 years (range [30][31][32][33][34][35][36][37][38][39][40] were exposed for 30 minutes under standard environmental conditions (T: 22˚C, 50% relative humidity) in the Controlled Environmental Research Laboratory (CE-Lab, Vision R&D, Valladolid Spain) in two separate visits (V1, V2) at least 24 hours apart. Saliva was collected after the exposure in each of the visits, and cortisol, α-amylase (sAA), secretory IgA (sIgA), testosterone, and soluble fraction of TNFα receptor II (sTNFαRII) were analyzed by ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…Fourteen participants in the study were men and twenty women. The median age was 35.4 years old (range [30][31][32][33][34][35][36][37][38][39][40].…”
Section: Sample Demographic Characteristicsmentioning
confidence: 99%
“…Following this, the individual chewed for another 5 min and the saliva produced collected at one minute intervals in a beaker using a funnel to help (Krasse 1988 ). The saliva collected was stored in a microcentrifuge tube with 1 µL of 0.1 M phenyl methane sulfonyl fluoride (PMSF) protease inhibitor (SIGMA-ALDRICH, Saint Louis, USA) (Bachtiar et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%